Impact of Remittance on Economic Growth in Bangladesh - Hasan, Sabiha Binta; Akhter, Roksana; Al Abbasi, Al Amin; Saha, Subrata (American Journal of Trade and Policy, 2019)
In Bangladesh, remittance is one of the most important economic variables in recent times as it has an impact on economic growth, helps in balancing balance of payments, increasing foreign exchange reserves, enhancing national savings and increasing velocity of money. For about two decades remittance has been contributing around 35% of export earnings. Moreover, it is greater than foreign aid and thus helps in lessening dependence on foreign aid remittance gets momentum in recent time in Bangladesh and is the second largest sector of foreign currency earnings after the garment; sector. If cost of imported raw materials is deducted from the foreign currency earning of the garments sector thanit becomes the largest sector of foreign currency earnings. Remittance earning ; increasing day by day but at a lower rate than the increase in emigration from Bangladesh due to the increasing share of unskilled or semi-skilled labors than the professionals in international migration. The share of remittance in GNI (Gross National Income) is increasing day by day. Remittance affects almost all the macro-economic indicators of a country positively. Though there are also negative sides of remittance earning e.g. brain drain, its overall contribution to Bangladesh economy is very much effective.